ANALISIS NILAI PH DAN INDEKS TELUR PUYUH SETELAH PERENDAMAN MENGGUNAKAN EKSTRAK LENGKUAS MERAH (Alpinia officinarum) TERFERMENTASI PADA KONSENTRASI YANG BERBEDA - Oktavianus Jehadut; Eka Fitasari; Rosyida Fajri Rinanti; Nurita Thiasari (Universitas Tribhuwana Tunggadewi, 2026)
This study aimed to evaluate the effect of fermented red galangal (Alpinia officinarum) extract on the pH value and index of quail eggs during storage. A total of 315 fresh quail eggs were subjected to three treatments: no immersion (P0), immersion in 25% extract (P1), and immersion in 50% extract (P2), using a completely randomized design with five replications. Eggs were immersed for 24 h and stored at room temperature for 0 to 49 days. Observations were conducted on days 0, 7, 14, 21, 28, 35, 42, and 49 for albumen pH, yolk pH, albumen index, and yolk index. The results showed that immersion in fermented red galangal extract significantly reduced the increase in pH of both albumen and yolk compared to the control, particularly at a concentration of 50%. The treatment also slowed the decline in albumen index and yolk index, with P2 consistently maintaining higher values throughout storage. Overall, immersion in 50% fermented red galangal extract was the most effective treatment, extending the internal quality of quail eggs for up to 49 days. This suggests that fermented red galangal extract has potential as a natural preservative for quail eggs, and further studies are recommended to assess microbiological quality and oxidative stability during storage.